Pengembangan Model Consignment Stock pada Sistem Rantai Pasok Dua Eselon dengan Permintaan Berfluktuasi dan Perubahan Order Awal - Ivan D. Wangsa; Bermawi P. Iskandar (Jurnal Teknik Industri: Jurnal Keilmuan dan Aplikasi Teknik Industri, 2013)
Scheduling changes on the production floor are common in practice to meet the consumer demand and these cause the nervousness. The nervousness in turn will result in increased costs and reduced service level. This research deals with  production batch size and buffer stock taking into account changes in a preliminary order. Change in the demand for a given day is announced one day before and this is viewed as it occurs randomly. This research was considered in two echelon supply chain system with a single supplier and single manufacturer. The development of model is transactional relationship and consignment stock contract relationship. This study also considers the backorder and production capacity according to the real condition. Numerical examples are given to demonstrate the performance of the models. From the numerical results, it appears that coefficient variation (CV) of the demand affects the results obtained using method of SM and LUC.